Pemberdayaan Kelompok Dasawisma dalam Meningkatkan Kemandirian Keluarga Melalui Semangat Kemerdekaan - Lilis Whyuni; Dewi Jannah (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Dasawisma groups have strategic potential in supporting family independence, but have not been optimally empowered. This Community Service activity aims to strengthen Dasawisma's capacity as agents of social change in enhancing family independence through the internalization of independence spirit values. The method used was a participatory and educational community organizing approach, implemented at Dasawisma Asoka RT.007, Bukit Timah Sub-district, Dumai City, on August 10, 2024. Activities included interactive material delivery, group discussions, work program preparation simulations, and reflective evaluations. The results showed increased understanding among Dasawisma members regarding their strategic roles, emergence of initiative and self-confidence, ability to formulate solutions based on local potential, and formation of more structured cooperation patterns and emergence of local mobilizer figures. The participatory approach based on independence values proved effective in driving Dasawisma's transformation from administrative implementers to subjects of independent and sustainable family and community development.